2021
DOI: 10.1080/0142159x.2021.1957088
|View full text |Cite
|
Sign up to set email alerts
|

Ottawa 2020 consensus statement for programmatic assessment – 1. Agreement on the principles

Abstract: Introduction: In the Ottawa 2018 Consensus framework for good assessment, a set of criteria was presented for systems of assessment. Currently, programmatic assessment is being established in an increasing number of programmes. In this Ottawa 2020 consensus statement for programmatic assessment insights from practice and research are used to define the principles of programmatic assessment. Methods: For fifteen programmes in health professions education affiliated with members of an expert group (n ¼ 20), an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 77 publications
0
70
0
2
Order By: Relevance
“…The sample included undergraduate and postgraduate programmes from six different countries across three continents. Following the Ottawa 2020 conference, the participants in the group who achieved consensus on the 12 principles of programmatic assessment (Heeneman et al 2021), plus one additional programme, were invited to complete a 16-item questionnaire about implementation of programmatic assessment.…”
Section: Participants and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample included undergraduate and postgraduate programmes from six different countries across three continents. Following the Ottawa 2020 conference, the participants in the group who achieved consensus on the 12 principles of programmatic assessment (Heeneman et al 2021), plus one additional programme, were invited to complete a 16-item questionnaire about implementation of programmatic assessment.…”
Section: Participants and Data Collectionmentioning
confidence: 99%
“…At the 2020 Ottawa conference, consensus was reached on twelve theoretical principles of programmatic assessment (Heeneman et al 2021). The consensus group, recognising the challenges of implementation (Norcini and Burch 2007;Norcini et al 2018), identified that, in order for programmatic assessment and its principles to exert their educational benefits, it is important to share a common understanding of how these principles are implemented across different contexts and regulatory settings.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings add to the existing debates about programmatic assessment in health professions education by suggesting that there are important and often neglected causal mechanisms that impact the students varied experiences during the implementation of programmatic assessment. This adds to the existing literature on implementation approaches involving complex, dynamic and multilevel systems 12,13 . Our findings add to the overarching causal mechanisms that can explain student experiences of programmatic assessment 12,13,56 .…”
Section: Discussionmentioning
confidence: 54%
“…The underlying theory and principles of programmatic assessment have been described in detail in the literature 7–11 . Notwithstanding, there is limited understanding of implementation approaches taken across different contexts that involve complex, dynamic and multilevel systems 12,13 . Few studies provide empirical data supported by theoretically informed explanations of how programmatic assessment is working, for whom and in what context? 14–16 This pragmatic approach is used in critical realist and realist evaluation, 17 contrasting with traditional approaches to assessment research that typically asks, “what works?” 18 There is thus a need to further develop appropriate research methodologies to ensure researchers are asking the appropriate questions when considering the impact of a complex educational intervention such as programmatic assessment 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The Swiss College of Surgeons intend to implement their new EPA-based core curriculum with the Surg-prEPAred app. Since the use of mobile technology for documenting WBA’s is also part of the newest consensus statements on assessment in medical education [ 19 , 20 ], several specialties in Switzerland are now using prEPAred to gain experience in working with EPAs. Several studies on this topic are on the way.…”
Section: Discussion and Further Workmentioning
confidence: 99%